SP0203 Molecular mechanisms of fibrogenesis in pulmonary fibrosis. (23rd January 2014) - Eickelberg, O.
Abstract : Interstitial lung diseases, most importantly idiopathic pulmonary fibrosis (IPF) share similar pathomechanistic principles, including progressive fibrosis of the pulmonary interstitium, distortion of normal lung architecture, and respiratory failure. Fibrotic alterations in IPF can occur secondary to acute or chronic lung injury. The prevalence and incidence of interstitial lung disease is often underestimated: up to 750.000 patients may suffer from interstitial lung disease in the Western World. IPF alone affects up to 150.000 patients in Europe and exhibits an average survival time of 3-5 years after diagnosis. This seminar will review initial trigger events and secondary hits in IPF, describe early cellular responses during the development of fibrosis, including regenerative responses, developmental pathways, cellular plasticity, trafficking and crosstalk, fibroblast activation, and matrix deposition. Finally, the seminar will highlight novel molecular concepts and targets for the treatment of fibrosis in general and IPF in particular. Disclosure of Interest: None Declared